(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2025)
This study provides a comprehensive review of the key advances in micropaleontological research of the Chubut Group in the Golfo San Jorge Basin during the twenty-first century, with a particular emphasis on the plant microfossil record of two critical stratigraphic units: the Pozo D-129 Formation and the Lago Colhué Huapi Formation. The Pozo D-129 Formation, which outcrops at the Sierra Silva anticline, contains gyrogonites and utricles belonging to the Characeae and Clavatoraceae families, as well as a palynoflora assemblage that includes primitive angiosperm pollen grains. The analyzed microfossil assemblages suggest a late early Aptian age for these deposits and provide valuable insights into the freshwater paleoenvironment, which developed under semiarid conditions. In contrast, the microfossil record from the upper levels of the Lago Colhué Huapi Formation, recovered from outcrops at the headwaters of the Río Chico, did not yield charophytes but revealed rich palynological assemblages, including several megaspores from the orders Salviniales, Isoetales, and Selaginellales, along with additional palaeobotanical remains such as charcoal. These findings significantly contribute to interpreting a late Maastrichtian age and facilitate the reconstruction of the vegetation that thrived in freshwater environments under warm and humid climatic conditions.